Periodontal disease and type I diabetes mellitus: Associations with glycemic control and complications - Ajita Meenawat; Karan Punn; Vivek Srivastava; Anand S Meenawat; R S Dolas; Vivek Govila (Wolters Kluwer Medknow Publications, 2013)
Objective: The aim of the study was to evaluate periodontal health status in patients diagnosed with type 1 diabetes mellitus (DM1) and to establish a correlation between metabolic control and periodontal health status. Materials and Methods: Periodontal health parameters namely plaque index (PI), gingival index (GI), probing pocket depth (PPD) and clinical attachment loss (CAL) were recorded in 28 patients diagnosed with type 1 diabetes mellitus (DM1) and 20 healthy controls. Diabetes history was recorded based on the information provided by the physician and it included date of diagnosis, duration, age of diagnosis, latest values of glycosylated haemoglobin and existing diabetic complications. Statistical analysis was performed to evaluate the relationship between periodontal parameters and degree of metabolic control, the duration of the disease and the appearance of complications. Results: The periodontal health in the diabetic group was compromised and they had greater bleeding index (P < 0.001), probing pocket depth (P < 0.001) and clinical attachment level (P = 0.001). Patients diagnosed for diabetes for shorter duration of time (4-7 years) showed bleeding index-disease severity correlation to be 1.760 ΁ 0.434. Conclusion: Periodontal disease was more evident in type 1 diabetes mellitus patients and periodontal inflammation is greatly increased in subjects with longer disease course, poor metabolic control and diabetic complications.